2020
DOI: 10.1098/rstb.2019.0639
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the power of fatty acids as dietary tracers and metabolic signals in fishes and aquatic invertebrates

Abstract: Determining the transfer and transformation of organic matter in food webs is a fundamental challenge that has implications for sustainable management of ecosystems. Fatty acids (FA) offer a potential approach for resolving complex diet mixtures of organisms because they provide a suite of molecular tracers. Yet, uncertainties in the degree of their biochemical modification by consumers, due to selective retention or metabolism, have limited their application. Here, we consolidated 316 controlled feeding studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 50 publications
3
39
0
Order By: Relevance
“…This pattern was particularly pronounced in DHA, where realized values of DHA in perch muscle tissue exceeded the theoretical values on average by a factor of five. Thus, our results are in-line with a recent meta-analysis of feeding studies in fish and aquatic invertebrates suggesting that DHA is retained even when supplied in high levels (Jardine et al 2020 ). Due to the important role of DHA in fish metabolism (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…This pattern was particularly pronounced in DHA, where realized values of DHA in perch muscle tissue exceeded the theoretical values on average by a factor of five. Thus, our results are in-line with a recent meta-analysis of feeding studies in fish and aquatic invertebrates suggesting that DHA is retained even when supplied in high levels (Jardine et al 2020 ). Due to the important role of DHA in fish metabolism (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…During larval development, DHA is preferentially incorporated into nervous and retina tissue (Izquierdo et al, 2000;Villalta et al, 2008), and growth anomalies and high mortality are observed when DHA is insufficient (Tocher, 2010). Other dietary FA, including linoleic acid (LA; 18:2n-6) and α-linolenic acid (LNA; 18:3n-3), are stored in muscle tissue to meet physiological needs and are also related to fish growth and survival to some extent (Jardine et al, 2020). These FA are precursors of DHA, EPA, and ARA, but as already pointed out; the activities of the specific enzymes (desaturase and elongase) responsible for their biosynthesis are limited in most marine species.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a key aspect of this approach is the adjustment of the predator's FA profile for these modifications. In QFASA applications, these modifications are taken into account using 'calibration coefficients' (CC) [13], defined as the ratio of the proportion of a FA in the predator's tissue relative to the proportion of the same FA in diet, after feeding the diet for a prolonged period [9]. While the basic biochemical processes that may occur are well known [12], the precise changes in FA concentration that arise from metabolism remain uncertain, making empirically derived CC essential.…”
Section: Introductionmentioning
confidence: 99%